THE MU’TAZILAH TAFSIR METHOD OF VERSES OF AQIDAH - Hanif, Muhammad; Rodiah, Rodiah; Sholeh, Zakiah Ulfah (JURNAL AL-AQIDAH, 2023)
Tafsir is a discipline in the study of the Qur'an which aims to understand the meaning and messages contained in the holy verses. One of the interpretation approaches that has been developed by the Mu'tazilah school of thought is the Mu'tazilah interpretation method. This method focuses on the interpretation of the verses of the Qur'an related to aqidah, namely beliefs in Islam. The purpose of this study is to dig deeper into the Mu'tazilah's method of interpretation of the verses of the Aqeedah, and to understand the main views used by Mu'tazilah scholars in their interpretation. Through a qualitative approach and literature analysis, this research involves an extensive literature study on the works and important views of Mu'tazilah scholars. The Mu'tazilah interpretation method emphasizes rationality and logic in the interpretation of aqidah verses. The Mu'tazilah scholars use a common sense approach, think critically, and reason logically to deal with the theological problems contained in these verses. They try to combine religious principles with those of philosophy and rationality. The results of this study reveal that the Mu'tazilah interpretation method of the verses of aqidah includes several main principles, such as the theory of God's justice, human freedom, rejection of absolute destiny, and the oneness of God. Mu'tazilah scholars also use linguistic approaches and historical contexts to understand the meaning of these verses. This study also highlights the influence and relevance of the Mu'tazilah interpretation method in the contemporary context. By understanding the Mu'tazilah interpretation method, readers can explore the thoughts and approaches used by the Mu'tazilah school in understanding the verses of the Aqeedah. This provides valuable insight into understanding the differences and variations in the exegesis of the Qur'an, as well as contributing to a more comprehensive understanding of aqeedah in Islam